2008
DOI: 10.1162/jocn.2008.20099
|View full text |Cite
|
Sign up to set email alerts
|

Involuntary Attentional Capture is Determined by Task Set: Evidence from Event-related Brain Potentials

Abstract: To find out whether attentional capture by irrelevant but salient visual objects is an exogenous bottom-up phenomenon, or can be modulated by current task set, two experiments were conducted where the N2pc component was measured as an electrophysiological marker of attentional selection in response to spatially uninformative colour singleton cues that preceded target arrays. When observers had to report the orientation of a uniquely coloured target bar among distractor bars (colour task), behavioural spatial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

35
323
5
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 319 publications
(364 citation statements)
references
References 20 publications
35
323
5
1
Order By: Relevance
“…As expected, behavioral spatial cuing effects indicative of attentional capture were observed on trials where target-color cues were presented. These cues also triggered pronounced N2pc components, confirming findings from previous ERP studies (Eimer & Kiss, 2008;Eimer et al, 2009;Lien et al, 2008) and emphasizing the fact that target-color cues captured attention. The critical question was whether similar behavioral and electrophysiological effects would also be observed for irrelevant-color cues.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…As expected, behavioral spatial cuing effects indicative of attentional capture were observed on trials where target-color cues were presented. These cues also triggered pronounced N2pc components, confirming findings from previous ERP studies (Eimer & Kiss, 2008;Eimer et al, 2009;Lien et al, 2008) and emphasizing the fact that target-color cues captured attention. The critical question was whether similar behavioral and electrophysiological effects would also be observed for irrelevant-color cues.…”
Section: Discussionsupporting
confidence: 88%
“…Under these conditions, inverted behavioral spatial cuing effects indicative of location-specific inhibition were reliably observed for irrelevant-color singleton cues; there was no evidence for an N2pc in response to these cues, suggesting that attentional capture was successfully prevented on virtually all trials. In contrast, results similar to those found in Experiment 2 (a small and delayed N2pc to irrelevant-color singleton cues in the absence of behavioral spatial cuing effects) were observed in another ERP experiment (Eimer & Kiss, 2008, Experiment 1) where observers searched for onset targets. These observations suggest that the impact of feature-specific top-down task sets on attentional selectivity may be generally more pronounced when visual search targets are nonsingletons.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The amplitude of this PCN wave typically is interpreted as indicating the amount of attentional-resource allocation required for a task, and its latency has been regarded as marking the transition from preattentive sensory coding to the stage of focal-attentional selection (18,19). Recently, the timing of the PCN has been shown to depend on a variety of factors, including bottom-up stimulus intensity (20) and saliency (21,22) as well as top-down featural (23) and dimensional set (24), illustrating the flexibility of human visuocortical processing as a function of external (stimulus) and internal (system) settings.…”
Section: Methodsmentioning
confidence: 99%
“…An argument put forward to favour this proposal is the observation that irrelevant distracters with a unique feature capture attention (Jonides and Yantis, 1988) or gaze (Theeuwes et al, 1999;van Zoest et al, 2004) and elicit electrophysiological responses preceding activity related to processing of the relevant target (Hickey et al, 2006). In contrast, other studies using similar paradigms found that stimulus relevance is a crucial determinant of attentional capture and may affect early cortical processing of visual stimuli (Eimer and Kiss, 2008;Leblanc et al, 2008;Ptak et al, 2011;Yantis and Egeth, 1999). For instance, the capture of attention by goal-relevant features modulates event-related potentials (ERPs) approximately 180 ms after stimulus onset (Leblanc et al, 2008).…”
Section: Introductionmentioning
confidence: 95%